2002
DOI: 10.1074/jbc.m109592200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Estrogen Receptor-α in Insulin-like Growth Factor-1 (IGF-1)-induced Uterine Responses and in Vivo Evidence for IGF-1/Estrogen Receptor Cross-talk

Abstract: In the uterus insulin-like growth factor-1 (IGF-1) signaling can be initiated by estradiol acting through its nuclear receptor (estrogen receptor (ER)) to stimulate the local synthesis of IGF-1. Conversely, in vitro studies have demonstrated that estradiol-independent ER transcriptional activity can be induced by IGF-1 signaling, providing evidence for a cross-talk mechanism between IGF-1 and ER. To investigate whether ER␣ is required for uterine responses to IGF-1 in vivo, both wild-type (WT) and ER␣ knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 33 publications
7
175
2
2
Order By: Relevance
“…Examples are insulin-like growth factor, epidermal growth factor, and transforming growth factor-beta, which act by binding to receptors on the cell membrane, and c-Fos and c-Jun, transcription factors that bind to AP-1 sites [9][10][11]25]. Cross-talk between these proteins and the five steroid receptors increases the combinatorial complexity for regulation of development in vertebrates.…”
Section: Steroids Regulate Gene Transcription In Many Tissues In Vertmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are insulin-like growth factor, epidermal growth factor, and transforming growth factor-beta, which act by binding to receptors on the cell membrane, and c-Fos and c-Jun, transcription factors that bind to AP-1 sites [9][10][11]25]. Cross-talk between these proteins and the five steroid receptors increases the combinatorial complexity for regulation of development in vertebrates.…”
Section: Steroids Regulate Gene Transcription In Many Tissues In Vertmentioning
confidence: 99%
“…1) [5][6][7][8], which is a ligand-based based mechanism for regulating the interactions between networks of transcription factors [9][10][11], as well as directly regulating the transcription of specific genes. Receptors for these steroids have not been found in invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 stimulates mitogenesis of the normal epithelium and proliferation of both endometrial cancers and leiomyoma cells (Strawn et al, 1995;Klotz et al, 2000). In the mouse uterine model, the in vivo proliferative response of IGF-1 requires ERa, even in the presence of a functional IGF-1 signaling response, as IGF-1 signaling to MAPK or Akt is unaffected by the loss of ER (Klotz et al, 2002). In the uterus, E2 increases the levels of IGF-1 mRNA, and stimulates tyrosine phosphorylation of the IGF-1 receptor and insulin receptor substrate-1, and the formation of IGF-1R signaling complexes (Richards et al, 1996;Klotz et al, 2000).…”
Section: Igf1-r Crosstalk With Er and Prmentioning
confidence: 99%
“…Our findings are in agreement with a previous study in ER␣ Ϫ/Ϫ mice, in which estrogen/ER␣ did activate the phosphorylation of AKT and lack of ER␣ did not produce phosphorylation of AKT in endometrial cells. 49 We also demonstrated that estrogen remodels the bladder detrusor through fibroblast activation, as characterized by increased fibroblast cell proliferation and altered collagen III synthesis. E 2 could modulate fibroblast activation via estrogen receptor, which was supported by the result that ICI could prevent the E 2 -induced activation in fibroblast culture.…”
Section: Discussionmentioning
confidence: 62%